Effective Search-Based Approach for Testing Non-Functional Properties in Software System: an Empirical Review - Bala, N.M.; Suhailan, S. (International Journal of Engineering and Technology, 2018)
Search-based software testing (SBST) is considered an effective process in the generation of non-functional test cases. The SBST employs metaheuristic search techniques to evaluate the best-case and worst-case execution times of real-time scenarios. However, these search techniques suffer software re-modularization for software systems. In this paper, an exploratory review on some of these techniques such as Genetic Algorithms, Harmony Search and Simulated Annealing is presented by highlighting the fitness function employed, non – functional testing and the challenges observed. The review also investigates each technique based on different applications employed in a white box, black-box, and gray-box testing. It shows that Harmony Search-Based Algorithm is the effective technique to address the problem of software re-modularization.